Wood, Trade, and Spanish Naval Power (c.1740-1795) - Reichert, Rafał B., (Brill's Series in the History of the Environment ;, 2024)
By focussing on timber sourcing, this book sheds light on the exploitation of forests in settings outside the Iberian Peninsula, including foreign states in the southern Baltic region and the colonial territory of New Spain between the c.1740-1795. Analysis of contracts, projects, and their implementation by the Spanish crown in the 18th century allow for a better understanding of the position of the Spanish monarchy's nearly global efforts to sustain its naval commitments in the Atlantic World.